Performance after concussion in National Hockey League players - Neustadtl, A. L.; Bukowski, W. K.; Neustadtl, A.; Milzman, D. (Journal of Athletic Training, 2021)
Context: Concussions in ice hockey players are an interesting area of study due to the fast-paced and high-impact nature of the sport. Recently, researchers have focused on player performance after return from concussion to evaluate subclinical deficits that were previously missed. Objective: To examine National Hockey League (NHL) player performance from 2013 to 2019 and compare performance before a concussion with performance immediately after recovering to assess the current NHL return-to-play protocol. Design: Cross-sectional study. Setting: The NHL Injury Viz and sports reporting websites. Patients or Other Participants: Players in the NHL who sustained concussions from 2013 to 2019. Main Outcome Measure(s): Goals, assists, points, plus-minus, time on ice (TOI), and hits. Results: When goals, assists, points, plus-minus, TOI, and hits were examined, only TOI was different after the players returned from injury, and this TOI difference was not substantively important. Conclusions: After concussion, NHL player performance did not change.